Comment on 'Unveiling ductile deformation during fast exhumation of a granitic pluton in a transfer zone' by Richard Spiess, Antonio Langone, Alfredo Caggianelli, Finlay M. Stuart, Martina Zucchi, Caterina Bianco, Andrea Brogi, & Domenico Liotta. (February 2022) - Mazzarini, F.; Musumeci, G.; Papeschi, S.
Abstract: In their paper, Spiess et al. (2021) published structural, geochronological, and EBSD data on one of the monzogranite apophyses (Capo Bianco) of the buried Porto Azzurro Pluton (island of Elba, Northern Apennines, Italy), a pluton emplaced in the upper crust (P < 0.2 GPa; e.g. Papeschi et al., 2019). The authors published a new U/Pb age of 6.4 ± 0.4 Ma, associated with the thermal peak, and a U-Th/He apatite age of 5.0 ± 0.6 Ma, indicating cooling below 60 °C. Spiess et al. (2021) use these ages to model the exhumation of the pluton controlled, in their model, by the Zuccale Fault, a subhorizontal fault with 6 km of eastward displacement (ZF; Keller & Coward, 1996). Their structural dataset from the macro to the microscale and EBSD analyses relies on a small section (about 100 m wide) in the NE part of the Calamita Peninsula. Based on their documentation of (1) vertical dykes in the monzogranite, (2) vertical to low-angle top-to-the-E extensional faults, and (3) later NW-striking oblique faults, they interpret the Porto Azzurro Pluton as emplaced in an extensional to transcurrent tectonic setting, extrapolating their findings to the entire Eastern Elba.